Mechanical and wear properties of nano titanium based dental composite resin - Vivek R.; Kumar A.; Chaturvedi T.P.; Prakash R. (My University, 2025)
The principle purpose among conservative dentistry researchers has been to restore missing tooth substance by a restorative material with significant harmonious properties like mechanical, physical, thermal, and wear properties. Toward this objective a number of materials have been long developed to emulate these properties. The improvements in the properties of polymethyl methacrylate (PMMA) composite as viable alternative compared with Hg based amalgam or other polymer composites with their positive clinical performance have been encouraged continuously over the years. Our chapter summarizes the study of mechanical and wear properties of PMMA resins modified by nano Ti fillers along with the recent gist of other dentistry materials. Herein we have synthesized 0.25%, 0.50%, 0.75%, and 1.0% nano Ti loaded nylon fiber reinforced PMMA (Ti/PMMA) composites to investigate the effect of nanofiller incorporation towards their thermal, tensile, and wear properties. © 2019 Elsevier Inc. All rights reserved.